Perceived risk of HIV infection among deported male injection drug users in Tijuana, Mexico - Pinedo, Miguel (Glob Public Health, 2014)
Deported injection drug users (IDUs) in Mexico may be vulnerable to HIV infection following expulsion from the U.S. We examined factors associated with HIV risk perception among a sample of deportees in Tijuana. From January to April 2010, 313 male IDUs who reported ever being deported from the U.S. completed a questionnaire. Overall, 35% (N=110) of deportees perceived HIV risk. In multivariate logistic regression analyses, factors independently associated with HIV risk perception included: ever having a steady female partner in Tijuana post-deportation (Adjusted Odds Ratio (AOR): 2.26; 95% Confidence Interval (CI): 1.01-5.07) and years spent in a U.S. prison (AOR: 1.29 per year; 95% CI: 1.13-1.48). Conversely, years of drug injection use (AOR: 0.95 per year; 95% CI: 0.91-0.99), ever witnessing family members use drugs prior to first migration trip (AOR: 0.24; 95% CI: 0.09-0.65), years of residence in the United States (AOR: 0.91 per year; 95% CI: 0.84-0.98) and being a Tijuana-native (AOR: 0.40; 95% CI: 0.16-0.99) were negatively associated HIV risk perception. U.S.-Mexico border cities that receive deported migrants should target HIV prevention interventions to specific subgroups, including drug-using male deportees. Interventions should consider migrant's time in the U.S., the role of their social networks, and reducing missed opportunities for HIV testing/education.